The mechanism of programmed death and endoplasmic reticulum stress in pulmonary hypertension - Yang Sun; Shasha Liu; Chen Chen; Songwei Yang; Gang Pei; Meiyu Lin; Ting Wang; Junpeng Long; Qian Yan; Jiao Yao; Yuting Lin; Fan Yi; et al. (Cell Death Discovery, 2023)
Abstract Pulmonary hypertension (PH) was a cardiovascular disease with high morbidity and mortality. PH was a chronic disease with complicated pathogenesis and uncontrollable factors. PH was divided into five groups according to its pathogenesis and clinical manifestations. Although the treatment and diagnosis of PH has made great progress in the past ten years. However, the diagnosis and prognosis of the PAH had a great contrast, which was not conducive to the diagnosis and treatment of PH. If not treated properly, it will lead to right ventricular failure or even death. Therefore, it was necessary to explore the pathogenesis of PH. The problem we urgently need to solve was to find and develop drugs for the treatment of PH. We reviewed the PH articles in the past 10 years or so as well as systematically summarized the recent advance. We summarized the latest research on the key regulatory factors (pyroptosis, apoptosis, necroptosis, ferroptosis, and endoplasmic reticulum stress) involved in PH. To provide theoretical basis and basis for finding new therapeutic targets and research directions of PH.